A Escola de Sargento das Armas: um estudo sociopolítico sobre a formação de praças do exército - Atassio, Aline Prado (2012)
This research aims at finding out about the perspectives of the future sergents of the Armed Force, graduated by the Escola de Sargento das Armas (EsSa). There are few studies about sergents within the Brazilian Social Science, therefore the importance of this research. Among the general focus of this research are the sergent history, their academic education within time and the quotidian os EsSa studentes. The study presents statistics that aims at showing the students´ social origin and interviews that present thestudents´ history and their longing about their career. We have used several scientific methods to conclude this theses, such as bibliographical research, semi-directed interviews, statistics and field research. The result has showed that most of the sergents are from low class families, from the south and south-west parts of Brazil, with age rate between 19 and 25 years-old, without militares parents and high-scholl graduated. However, they don´t show either greater oportunities of advance in theis studies neither possibilities of garantee a career outside the Arm. This confirms the theses that the Arm is used, historically, as a mean of social scaling form those that are in the lower part of Brazilian social pyramid.